Using repeated visual exposure, rewards and modelling in a mobile application to increase vegetable acceptance in children. (1st October 2019) - Farrow, Claire; Belcher, Esme; Coulthard, Helen; Thomas, Jason M.; Lumsden, Joanna; Hakobyan, Lilit; Haycraft, Emma
Abstract: Children are not consuming the recommended amounts of fruit and vegetables. Repeated visual exposure, modelling, and rewards have been shown to be effective at increasing vegetable acceptance in young children. The aim of this study was to assess the effectiveness of an evidence-based mobile application (Vegetable Maths Masters) which builds on these principles to increase children's liking and acceptance of vegetables. Seventy-four children (37 male, 37 female) aged 3–6 years old were randomised to play with either the vegetable app or a similar control app that did not include any foods. Children played their allocated game for 10 min. Liking and acceptance of the vegetables used in Vegetable Maths Masters (carrot and sweetcorn) and other vegetables which were not used in the game (yellow pepper and tomato) were measured pre- and post-play in both groups. Parents provided data about their child's food fussiness and previous exposure to the foods being used. Children who played with the Vegetable Maths Masters app consumed significantly more vegetables after playing with the app and reported significant increases in their liking of vegetables, relative to the control group. The effect of the Vegetable Maths Masters app on the change in consumption of vegetables was mediated by the change in liking of vegetables. These findings suggest that evidence-based mobile apps can provide an effective tool for increasing children's liking and consumption of vegetables in the short-term. Further work is now required to establish whether these effects are maintained over time. Highlights: A vegetable based maths game was developed to support vegetable accetpance using the principles of repeated exposure, modelling, and rewards. Playing with the Vegetable Maths Maters app for 10 min resulted in significant increases in liking and intake of vegetables in 3–6 year old children. Increases in consumption of vegetables were explained by increases in liking for vegetables after children played with the app. Future research is needed to explore the effectiveness of such games in the longer term.